ANALYSIS OF THE IMPLEMENTATION OF DIGITAL MARKETING AND MARKETPLACES ON THE DEVELOPMENT OF MSME INCOME IN MEDAN CITY - Misna Doharni Harahap; Wahyu Ario Pratomo; Irsad (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of Digital Marketing and Marketplace on the Revenue of Micro, Small, and Medium Enterprises (MSMEs) with Sales as an intervening variable in Medan City. The rapid growth of the digital economy has significantly changed marketing patterns and consumer behavior, thus encouraging MSMEs to adapt to technological developments to remain competitive. Digital marketing allows businesses to promote products effectively through social media such as Instagram, Facebook, and TikTok, while marketplace platforms such as Shopee and Tokopedia provide wider market access and ease of transactions. This study uses a quantitative approach with a purposive sampling technique, involving 384 MSME respondents who have been operating for at least one year and actively utilize social media and marketplaces in marketing and sales activities. Primary data was obtained through a questionnaire with a Likert scale, then analyzed using the Partial Least Square (PLS) method to test the direct, indirect, and mediating effects between variables. The results show that Digital Marketing has a positive and significant effect on MSME Sales and Revenue. Similarly, Marketplace has a positive effect on Sales, which ultimately increases MSME Revenue. The Sales variable is proven to act as a mediating variable that strengthens the relationship between Digital Marketing and Marketplace on MSME Revenue. These findings indicate that the more intensively MSMEs implement digital marketing strategies and utilize marketplaces, the greater their ability to increase revenue in a stable and sustainable manner. This research provides theoretical and practical contributions to the development of literature on digital marketing and the capacity building of MSMEs in the digital economy era. The results can serve as a reference for businesses, the government, and supporting institutions in designing digital training policies, business mentoring, and strategic collaboration with marketplace platforms to drive sustainable regional economic growth.